Numerical solution for consistent initial conditions of constrained mechanical systems - Phong, Dinh Van (Vietnam Journal of Mechanics, 2003)
The article deals with the problem of consistent initial values of the system of equations of motion which has the form of the system of differential-algebraic equations. Direct treating the equations of mechanical systems with particular properties enables to study the system of DAE in a more flexible approach. Algorithms and examples are shown in order to illustrate the considered technique.